The Influence of Learning by Smartphone to the Conceptual Science Knowledge and the Independence of Students’ Learning at Junior High School - Hasanah, Ibadul; Hasani, Aceng; Fatah, Abdul; Sari, Indah Juwita; Romdani, Andhy (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to determine the effect of using smart phone learning on science knowledge conceptual and independence of students’ learning in junior high school. The design of quadratic control groups is used on this research with all seventh grade students at Serang-Banten City Junior High School as the population. The random technique samples are VII A grade as an experimental class and VII B grade as the control class, so it can be measured the conceptual science knowledge and scaling the independence of students’ learning by questionnaire. Independent sample T Test survey result shows using the smart phone has an impact to science knowledge with a significance value of 0.002 and an independence of student’s learning with a significance value of 0.003.